2020
DOI: 10.1017/wet.2020.12
|View full text |Cite
|
Sign up to set email alerts
|

Potential yield loss in grain sorghum (Sorghum bicolor) with weed interference in the United States

Abstract: Potential yield losses in grain sorghum due to weed interference based on quantitative data from the major grain sorghum-growing areas of the United States are reported by the WSSA Weed Loss Committee. Weed scientists and extension specialists who researched weed control in grain sorghum provided data on grain sorghum yield loss due to weed interference in their region. Data were requested from up to 10 individual experiments per calendar year over 10 yr between 2007 and 2016. Based on the summarized informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
2
28
1
2
Order By: Relevance
“…Graham et al [44] reported that high weed density negatively affected leaf area and light absorption, resulting in affected crop yield. These results support Dille et al [45], who reported that approximately 47% of sorghum total yield was lost due to weed interference.…”
Section: Discussionsupporting
confidence: 91%
“…Graham et al [44] reported that high weed density negatively affected leaf area and light absorption, resulting in affected crop yield. These results support Dille et al [45], who reported that approximately 47% of sorghum total yield was lost due to weed interference.…”
Section: Discussionsupporting
confidence: 91%
“…Yield losses from 37% to 61% were reported by Dille, et al [1] in grain sorghum with weed interference in different regions of the United States. The results from field studies showed that growers in different regions of the United States and Canada would potentially lose an average of 31% to 94% of their dry bean yield [2] and 61% to 83% of the sugar beet yield [3] due to weeds.…”
Section: Introductionmentioning
confidence: 90%
“…verticilliflorum [46]. While sudangrass can be grown as a forage crop, shattercane is a weedy relative of sorghum that is a considered a serious weed whose agronomic importance has increased over the years [14,26,27,31,46,[49][50][51].…”
Section: Originmentioning
confidence: 99%
“…All reports of yield loss due to shattercane competition are from field trials conducted in the United States, with the exception of the case study by Raey et al [27], which was conducted in Iran, Asia (Table 1). Especially in the United States, shattercane is one of the most common and problematic weeds in grain sorghum [50]. There are also case studies from this continent showing the competitive ability of shattercane against domesticated sorghum and other important summer field crops.…”
Section: Competitive Ability and Distributionmentioning
confidence: 99%